Retratamiento no quirúrgico de fracasos endodónticos: Parte I - Pineda Mejia, Martha Elena (2003)
In this report it is made a revision about success and failure in endodontics. The main causes of root canal treatment failure are described: periodontal, prosthetics or restoring und endodontic ones. The main retreatment indications are exposed outlining the necessity of this, not only in those cases where there are unequivocal symptoms of failure, but also in those asymptomatic teeth with a dubious root canal filling, which need a new prosthetic treatment or restoring.